Paired Donor and Recipient Immunophenotyping in Allogeneic Hematopoietic Stem Cell Transplantation: A Cellular Network Approach - Wittenbecher, Friedrich; Lesch, Stella; Kolling, Stefan; Blau, Igor-Wolfgang; Vuong, Lam; Borchert, Franziska; Movasshagi, Kamran; Tietze-Bürger, Carola; Penack, Olaf; Ahn, Johann; Bullinger, Lars; Frentsch, Marco; et al. (Frontiers in Immunology, 2022)
Success and complications of allogeneic hematopoietic stem cell transplantation (alloHSCT) are closely connected to the transferred graft and immune reconstitution post alloHSCT. Due to the variety of immune cells and their distinct roles, a broad evaluation of the immune cellular network is warranted in mobilization and reconstitution studies in alloHSCT. Here, we propose a comprehensive phenotypic analysis of 26 immune cell subsets with multicolor flow cytometry from only 100µl whole blood per time point. Using this approach, we provide an extensive longitudinal analysis of almost 200 time points from 21 donor-recipient pairs. We observe a broad mobilization of innate and adaptive immune cell subsets after granulocyte colony-stimulating factor (G-CSF) treatment of healthy donors. Our data suggest that the relative quantitative immune cell subset composition in recipients approaches that of healthy donors from day +180 post alloHSCT onwards. Correlation of donor and recipient cell counts reveals distinct association patterns for different immune cell subsets and hierarchical clustering of recipient cell counts identifies distinct reconstitution groups in the first month after transplantation. We suggest our comprehensive immune subset analysis as a feasible and time efficient approach for a broad immune assessment for future clinical studies in the context of alloHSCT. This comprehensive cell composition assessment can be a critical step towards personalized graft composition strategies and individualized therapy management in areas such as GvHD prophylaxis in the highly complex immunological setting of alloHSCT.